THE METHODOLOGICAL ISSUES OF SUPPORT MANAGEMENT DECISIONS IN INTERNATIONAL MARKETING MANAGEMENT OF AVIATION ENTERPRISE - Solopenko, T. R. (Science and Transport Progress, 2007)
The questions of economic ground of administrative decisions are affected, related from by the Marketing management of aviation enterprise, methods are examined economic of administrative decisions, and utilizinga mathematical design for constructions of optimization models and their realization automated control the system «Marketing of aviation enterprise» on a base automated control the system (TO THE ACE) by an aviation enterprise.